Risk of subsequent primary lymphoma in a cohort of 69, 460 five‐year survivors of childhood and adolescent cancer in Europe: The PanCareSurFup study. Issue 3 (29th November 2022) - Dudley, Isabelle M.; Sunguc, Ceren; Heymer, Emma J.; Winter, David L.; Teepen, Jop C.; Belle, Fabiën N.; Bárdi, Edit; Bagnasco, Francesca; Gudmundsdottir, Thorgerdur; Skinner, Roderick; Michel, Gisela; Byrne, Julianne; et al.
Abstract: Background: Survivors of Hodgkin lymphoma (HL) are at risk of developing non‐Hodgkin lymphoma (NHL) after treatment; however, the risks of developing subsequent primary lymphomas (SPLs), including HL and NHL, after different types of childhood cancer are unknown. The authors quantified the risk of SPLs using the largest cohort of childhood cancer survivors worldwide. Methods: The Pan‐European Network for Care of Survivors After Childhood and Adolescent Cancer (PanCare) Survivor Care and Follow‐Up Studies (PanCareSurFup) cohort includes 69, 460 five‐year survivors of childhood cancer, diagnosed during 1940 through 2008, from 12 European countries. Risks of SPLs were quantified by standardized incidence ratios (SIRs) and relative risks (RRs) using multivariable Poisson regression. Results: Overall, 140 SPLs, including 104 NHLs and 36 HLs, were identified. Survivors were at 60% increased risk of an SPL compared with the general population (SIR, 1.6; 95% confidence interval [CI], 1.4–1.9). Survivors were twice as likely to develop NHL (SIR, 2.3; 95% CI, 1.9–2.8), with the greatest risks among survivors of HL (SIR, 7.1; 95% CI, 5.1–10.0), Wilms tumor (SIR, 3.1; 95% CI, 1.7–5.7), leukemia (SIR, 2.8; 95% CI, 1.8–4.4), and bone sarcoma (SIR, 2.7; 95% CI, 1.4–5.4). Treatment with chemotherapy for any cancer doubled the RR of NHL (RR, 2.1; 95% CI, 1.2–3.9), but treatment with radiotherapy did not (RR, 1.2; 95% CI, 0.7–2.0). Survivors were at similar risk of developing a subsequent HL as the general population (SIR, 1.1; 95% CI, 0.8–1.5). Conclusions: In addition to HL, the authors show here for the first time that survivors of Wilms tumor, leukemia, and bone sarcoma are at risk of NHL. Survivors and health care professionals should be aware of the risk of NHL in these survivors and in any survivors treated with chemotherapy. Abstract : Using data from 69, 460 five‐year survivors of childhood cancer across Europe, the authors investigated the risks of subsequent primary lymphoma within the largest cohort reported to date. Novel findings include the identification of an increased risk of non‐Hodgkin lymphoma among survivors of Wilms tumor, leukemia, and bone sarcoma and in any survivors treated with chemotherapy.